Microscale extraction method for HPLC carotenoid analysis in vegetable matrices - Pacheco,Sidney (2014)
In order to generate simple, efficient analytical methods that are also fast, clean, and economical, and are capable of producing reliable results for a large number of samples, a micro scale extraction method for analysis of carotenoids in vegetable matrices was developed. The efficiency of this adapted method was checked by comparing the results obtained from vegetable matrices, based on extraction equivalence, time required and reagents. Six matrices were used: tomato (Solanum lycopersicum L.), carrot (Daucus carota L.), sweet potato with orange pulp (Ipomoea batatas (L.) Lam.), pumpkin (Cucurbita moschata Duch.), watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai) and sweet potato (Ipomoea batatas (L.) Lam.) flour. Quantification of the total carotenoids was made by spectrophotometry. Quantification and determination of carotenoid profiles were formulated by High Performance Liquid Chromatography with photodiode array detection. Microscale extraction was faster, cheaper and cleaner than the commonly used one, and advantageous for analytical laboratories.